Mechanical ventilation-associated complications and comorbidities in children admitted at pediatric intensive care unit: A cross-sectional retrospective study - Amany Mohammed El-Rebigi; Amany Nagah Fekry; Maha A. Elfaramawy; Rasha Mohammed Zakaria (Turkish Journal of Emergency Medicine, 2025)
OBJECTIVES: Mechanical ventilation (MV) is frequently employed in acute care settings for severely ill children, but it may be associated with adverse events (AEs). This study investigated the AEs and comorbidities in children receiving invasive MV (IMV). METHODS: This retrospective cross-sectional study assessed pediatric patients admitted to the pediatric intensive care unit from January 2021 to December 2023 and received IMV. Demographics, clinical findings, concurrent medical conditions, ventilator settings, complications, and outcomes were collected. The predictors of MV-related AEs were assessed using multivariate logistic regression. RESULTS: One-quarter (24.1%) of the patients experienced at least one AE. Ventilator-associated pneumonia (VAP) was the most common consequence (13%), followed by postextubation stridor (7.9%) and air-leak syndrome (pneumothorax) (6%). Only 12.4% of cases had comorbidities and the death rate was 9.8%. The factors significantly associated with AEs included nonrespiratory causes for admission, prolonged MV duration, and the presence of comorbidities. CONCLUSIONS: There is an elevated incidence of AEs, with VAP being the most frequent. Nonrespiratory causes for admission, prolonged MV, and preexisting comorbidities were the main predictors of AEs.